Profile of Toulmin’s Scientific Arguments Students and Technological Utilities in Global Warming Topic - Arif Rahman Hakim; Wahono Widodo; Titin Sunarti (JPPS (Jurnal Penelitian Pendidikan Sains), 2022)
Research aims to determine the profile of  Toulmin’s Scientific Argument on students' and Technological Utilities  In Global Warning Topic. This research is a quantitative descriptive study using the observation method. Data is collected through observation, validation, tests, and questionnaires for student responses. The analysis of students' argumentation skills was carried out by observing the learning process and giving a written test conducted in students of senior high school. According to Toulmin, the assessment of students' argumentation skills refers to the measurement of argumentation skills, which includes components of claim, data, warrant, rebuttal, and backing. Based on the results of the study, it can be concluded that the Toulmin’s Scientific Arguments students and Technological Utilities are still relatively low, Toulmin Scientific Arguments students skills are at level 2, dominated by the most claims originating from scientific data/concepts and experience as well as personal observations of the environment and the use of technology in learning is still not optimal to improve Toulmin’s Scientific Arguments Students. Hence, it is necessary to provide innovative learning that can optimally improve Toulmin’s Scientific Arguments.